Individual variations in pre-altitude hemoglobin mass influence hemoglobin mass responses to repeated altitude sojourns - Skattebo, Ø.; Hallén, J. (Scandinavian Journal of Medicine & Science in Sports, 2022)
Introduction: Previous studies have shown variable within-subject hemoglobin mass (Hbmass) responses to altitude training. We investigated whether Hbmass responses depend on individual variations in pre-altitude Hbmass during repeated altitude sojourns. Methods: Nine elite endurance athletes carried out 3-5 altitude sojourns over 17 ± 10 months (mean ± 95% confidence interval), at an altitude of 1976 ± 62 m, for 21 ± 1 days, and a total hypoxic dose of 989 ± 46 km·h, with Hbmass assessed before and after each sojourn (carbon monoxide rebreathing). The individual mean baseline was calculated as the mean of all pre-altitude Hbmass values for an athlete, and it was investigated whether the percent deviation from the individual mean baseline affected the altitude-induced Hbmass response. Results: On average, Hbmass increased by 3.4 ± 1.1% (p < 0.001) from pre- to post-altitude. The intra-individual changes in Hbmass were highly inconsistent (coefficient of variation, CV: 88%), and we found no relationship between Hbmass changes in successive altitude sojourns (r = 0.01; p = 0.735). However, the percent increase in Hbmass was highly correlated with the pre-altitude Hbmass, expressed as the percent deviation from the individual mean baseline (y = -0.7x + 3.4; r = 0.75; p < 0.001). Linear mixed-model analysis confirmed a -0.6 ± 0.2% smaller increase in Hbmass for each 1% higher pre-altitude Hbmass than the individual mean baseline (p < 0.001) after adjusting for the covariates hypoxic dose (p = 0.032) and the relative Hbmass (g·kg-1 body weight; p = 0.031). Conclusion: Individual variations in pre-altitude Hbmass significantly influence the athletes' Hbmass responses to repeated altitude sojourns, with a potentiated response after traveling to altitude with a low pre-altitude Hbmass.